Whole grain intake compared with cereal fibre intake in association to CVD risk factors: a cross-sectional analysis of the National Diet and Nutrition Survey (UK). Issue 8 (19th June 2020) - Barrett, Eden M; Amoutzopoulos, Birdem; Batterham, Marijka J; Ray, Sumantra; Beck, Eleanor J
Abstract: Objective: To investigate how intakes of whole grains and cereal fibre were associated to risk factors for CVD in UK adults. Design: Cross-sectional analyses examined associations between whole grain and cereal fibre intakes and adiposity measurements, serum lipid concentrations, C-reactive protein, systolic blood pressure, fasting glucose, HbA1c, homocysteine and a combined CVD relative risk score. Setting: The National Diet and Nutrition Survey (NDNS) Rolling Programme 2008–2014. Participants: A nationally representative sample of 2689 adults. Results: Participants in the highest quartile (Q4) of whole grain intake had lower waist–hip ratio (Q1 0·872; Q4 0·857; P = 0·04), HbA1c (Q1 5·66 %; Q4 5·47 %; P = 0·01) and homocysteine (Q1 9·95 µmol/l; Q4 8·76 µmol/l; P = 0·01) compared with participants in the lowest quartile (Q1), after adjusting for dietary and lifestyle factors, including cereal fibre intake. Whole grain intake was inversely associated with C-reactive protein using multivariate analysis ( P = 0·02), but this was not significant after final adjustment for cereal fibre. Cereal fibre intake was also inversely associated with waist–hip ratio ( P = 0·03) and homocysteine ( P = 0·002) in multivariate analysis. Conclusions: Similar inverse associations between whole grain and cereal fibre intakes to CVD risk factors suggest the relevance of cereal fibre in the protective effects of whole grains. However, whole grain associations often remained significant after adjusting for cereal fibre intake, suggesting additional constituents may be relevant. Intervention studies are needed to compare cereal fibre intake from non-whole grain sources to whole grain intake.